PENGARUH TERAPI RENDAM KAKI MENGGUNAKAN AIR HANGAT DENGAN AROMATERAPI LAVENDER TERHADAP INSOMNIA PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Fora Rosna Zendrato; Muhammad Taufik Daniel Hasibuan (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Insomnia is a common issue among breast cancer patients undergoing chemotherapy due to the side effects of treatment, stress, and hormonal changes. Non-pharmacological therapies, such as warm water foot soak combined with lavender aromatherapy, may serve as an alternative solution to improve sleep quality. Objective: To determine the effect of warm water foot soak therapy with lavender aromatherapy on the level of insomnia in breast cancer patients undergoing chemotherapy at Murni Teguh Memorial Hospital. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 breast cancer patients experiencing moderate to severe insomnia, selected using purposive sampling. The intervention involved a daily 15minute warm water foot soak with lavender aromatherapy for a specific period. Insomnia levels were measured before and after the intervention using the Insomnia Severity Index (ISI) questionnaire. Data analysis was performed using statistical tests to assess changes in insomnia levels before and after the therapy. Results: The findings indicated a significant difference in insomnia levels before and after the warm water foot soak therapy with lavender aromatherapy (p < 0.05). Most participants experienced a reduction in insomnia levels following the intervention. Conclusion: Warm water foot soak therapy combined with lavender aromatherapy is proven to be effective in reducing insomnia in breast cancer patients undergoing chemotherapy. This therapy can serve as a safe and easy-to-apply complementary method to improve patients' sleep quality.